South-South Cross-Border Marriage Between Chinese Men and Ethiopian Women (African Human Mobility Review, 2023)
This article develops an ideal type of South-South cross-border marriage. Based on an eight-month multi-sited ethnography in Ethiopia and China, I identified an unusual conjuncture of global forces, connections, and imaginations that facilitated cross-border marriages between Chinese men and local women in Ethiopia, which should be considered a novel ideal type. Its theoretical novelty is not only defined by the unique dynamics among Sino-Ethiopian spouses vis-à-vis the “segregated” Chinese documented in existing studies but also by these marriages’ distinct formation mechanisms. Sino-Ethiopian marriage is not formed due to China being an attractive destination but is associated with China’s incompatible hard and soft power as forces, Chinese factories and accumulated Sino-Ethiopian social networks in local communities as connections, and localized imaginations. Furthermore, this study calls for a paradigm shift in examining cross-border marriages between a developing South and a rising South in this dramatically changing global capitalist world system.